Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1994
DOI: 10.1161/01.cir.89.2.740
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional left ventricular deformation during systole using magnetic resonance imaging with spatial modulation of magnetization.

Abstract: Consistent regional variations in deformation are seen in the normal human heart. Displacement and maximum shortening strains are well characterized with two-dimensional magnetic resonance tagging; however, higher-resolution images will be required to study transmural variations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
83
0
2

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(98 citation statements)
references
References 27 publications
(7 reference statements)
13
83
0
2
Order By: Relevance
“…Generally, the shortening of the longitudinal (base-apex) axis is approximately 20 mm in normal subjects (10). In addition, regional heterogeneity of LV longitudinal shortening has been shown in normal volunteers (11)(12)(13) and in patients with heart disease (14). In the experiment, our results also demonstrated that the longitudinal shortening of LV myocardium was greater in posterior and lateral walls and less in anterior and septal walls.…”
Section: Discussionsupporting
confidence: 68%
“…Generally, the shortening of the longitudinal (base-apex) axis is approximately 20 mm in normal subjects (10). In addition, regional heterogeneity of LV longitudinal shortening has been shown in normal volunteers (11)(12)(13) and in patients with heart disease (14). In the experiment, our results also demonstrated that the longitudinal shortening of LV myocardium was greater in posterior and lateral walls and less in anterior and septal walls.…”
Section: Discussionsupporting
confidence: 68%
“…The regional deformations of the myocardium were then characterized by using homogeneous finite strain analysis on the deforming triangles 6,17,18,24 -27 with the strain software module of VIDA. 21 This methodology has been validated in a phantom 14 and used in vivo by Young et al 27 These studies demonstrated that homogeneous strain analysis produced unbiased estimates of the principal strains, principal angles, and orientations of the principal axes.…”
Section: Image and Data Analysismentioning
confidence: 99%
“…17 Briefly, Delaunay triangulation of the tagged intersections was used to compute uniform triangles across the wall. 22,23 Continuum mechanics mathematics, which characterized the complex deformation patterns of the myocardium, 25 has been described and used by us 6,17,18 and others, 27 by using homogeneous finite strains to characterize 2-dimensional shape changes of the magnetically tagged grids. As we have noted, this approach assumed that deformations within each triangle relative to end-diastole were locally homogeneous (Figure 1).…”
Section: Homogeneous Finite Strain Analysismentioning
confidence: 99%
“…Both approaches are easily applicable on standard clinical scanners. Data acquired with tagging provide information with respect to muscle deformation (2,3,(9)(10)(11)(12)(13)(14)(15)(16). While easy to visualize and implement, tagging methods suffer from low spatial resolution.…”
mentioning
confidence: 99%